Strategi Kepemimpinan Transformasional untuk Meningkatkan Mutu Layanan Pendidikan Islam - Dicky Artanto (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2022)
Leadership in Islamic educational institutions is a very important thing to study in depth. The impact of a leadership can result in the back and forth of the quality of service of an institution or institution it leads. There are several leadership models that can be applied, one of which is transformational leadership, where this model is oriented towards better change for the institution. This research examines related to transformational leadership in improving the quality of educational services at STAIT Yogyakarta. This research method uses field research, namely field research at STAIT Yogyakarta, by interviewing several respondents, namely the Chairman, Lecturers, and Employees of STAIT Yogyakarta, field observation, and documentation analysis using data in the form of documents and related data sources needed. Data analysis using the Miles and Huberman methods is by data collection, data reduction, data presentation, and inference or data verification. Based on the results of the study, it can be concluded that the leadership at STAIT Yogyakarta puts forward the aspect of change innovation where the chairman of STAIT Yogyakarta always tries to provide encouragement, and motivation to the entire community to be oriented towards institution development and institutional change. It is proven that the ideals of change that are now being worked on by STAIT Yogyakarta are revitalization and restoration of the construction of a new building on Jalan Wates Yogyakarta.